Interannual modulations in sea level rise over tropical Northwest Pacific in satellite altimeter measurements - Uppara, Umakanth; Moon, Jae-Hong; Jang, Chan Joo; Jo, Young-Heon (Frontiers in Marine Science, 2023)
The sea level rise (SLR) estimates in tropical Pacific are dominantly influenced by interannual and interdecadal variations in limited data sets such as satellite altimeter measurements. The Sea Level Anomaly (SLA) trends during 1993–2012 (extensively reported) and 1993–2020 significantly differ with substantial weakening during 1993–2020 over tropical Northwest Pacific (NWP; 0–15°N; 120°E −170°E). An ensemble empirical mode decomposition (EEMD) approach is employed to derive residual SLA by removing the high-frequency SLA variations including the interannual and interdecadal variations. The linear trends estimated from residual SLA provides a better estimate for the trends in SLA. The residual trends have greatly reduced the observed differences in SLA trends between 1993–2012 and 1993–2020. Our analysis suggests that it is the interdecadal variations in SLA that caused the weakening of overall trend during 1993–2020. In particular, the interdecadal trend in SLA over NWP is ≈ −1.73 mm year−1, whereas the trends in total and the residual SLA are estimated as 4.26 mm year−1 and 6.32 mm year−1, respectively. Furthermore, it is observed that there is an in-phase connection between the interannual and the interdecadal variations of SLA associated with La Niña compared with El Niño. Therefore, the non-occurrence of La Niña after 2012 to 2020 possibly has contributed for the decreasing trend in interdecadal variations due to its in-phase connection. In short, the complexity of variations in SLA at different timescales over NWP and the Pacific significantly influences the SLA trend estimates.